2009
DOI: 10.1897/08-578.1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the genetic consequences of environmental toxicant exposure: Chernobyl as a model system

Abstract: Abstract-We sampled vole populations in Ukraine with the dual goal of characterizing population diversity and of providing a biogeographic perspective to evaluate experimental designs used for previous studies. Our data indicate that genetic diversity in bank vole populations is widely variable across regions and that diversity estimates in contaminated sites are unremarkable compared to those in uncontaminated areas. Furthermore, the relative frequencies of haplotypes have remained statistically identical thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 71 publications
(122 reference statements)
1
16
0
Order By: Relevance
“…Despite the availability of over 1,000 mtDNA control region sequences sampled from individuals of C. glareolus from multiple studies (see Table 1 and Supporting Information Appendix S2), use of these sequences has primarily been restricted to investigating the associated Puumala virus (Dekonenko et al, 2003;Johansson et al, 2008;Razzauti, Plyusnina, Niemimaa, Henttonen, & Plyusnin, 2012) or the effects of Chernobyl radiation (Matson, Rodgers, Chesser, & Baker, 2000;Meeks et al, 2007;Meeks, Chesser, Rodgers, Gaschak, & Baker, 2009;Wickliffe et al, 2006) on C. glareolus. Figure 2b indicates diversity values generally reflective of the aforementioned complexity; however, regionally restricted sampling does not enable accurate phylogeographical inferences to be made using the control region sequences available here.…”
Section: Clethrionomys [= Myodes] Glareolusmentioning
confidence: 99%
“…Despite the availability of over 1,000 mtDNA control region sequences sampled from individuals of C. glareolus from multiple studies (see Table 1 and Supporting Information Appendix S2), use of these sequences has primarily been restricted to investigating the associated Puumala virus (Dekonenko et al, 2003;Johansson et al, 2008;Razzauti, Plyusnina, Niemimaa, Henttonen, & Plyusnin, 2012) or the effects of Chernobyl radiation (Matson, Rodgers, Chesser, & Baker, 2000;Meeks et al, 2007;Meeks, Chesser, Rodgers, Gaschak, & Baker, 2009;Wickliffe et al, 2006) on C. glareolus. Figure 2b indicates diversity values generally reflective of the aforementioned complexity; however, regionally restricted sampling does not enable accurate phylogeographical inferences to be made using the control region sequences available here.…”
Section: Clethrionomys [= Myodes] Glareolusmentioning
confidence: 99%
“…The indicators of the genetic diversity reflected some intra-population processes and natural history of each population. Moreover, the genetic diversity of the Myodes glareolus species in Ukraine also appeared to vary significantly, and consequently, genetic features of the vole's sub-population in the ChEZ do not differ from those attributed to this species overall (Meeks et al 2009).…”
Section: Ecotoxicological Studiesmentioning
confidence: 95%
“…Several studies have quantified mitochondrial diversity (at a 291‐bp fragment of the control region and some adjacent tRNA) in bank voles inhabiting the CEZ and in uncontaminated sites in Ukraine (Matson, Rodgers, Chesser, & Baker, ; Meeks et al., , ; Wickliffe et al., ): none of these studies concluded that there was a robust association between mutation rate and the level of environmental radionuclides. Rather, studies have highlighted the need for additional sampling (Matson et al., ; Wickliffe et al., ) or found mitochondrial diversity to be comparable between contaminated and uncontaminated sites that were located close to the CNPP (Meeks et al., ); moreover, genetic diversity was heterogeneous among samples of bank voles collected over a large area of Ukraine, with uncontaminated locations containing more unique haplotypes and a higher ratio of unique to total haplotypes (Table in Meeks et al., ). Variation in mitochondrial diversity in bank voles has been explained by demographic and ecological processes, rather than exposure to environmental radionuclides (e.g., Meeks et al., ).…”
Section: Sampling: Unclear Choice Of Control Sitesmentioning
confidence: 99%
“…The bank vole is a small rodent that is common in forest habitats in northern Europe. As this species is common within and around the CEZ, the bank vole has been widely studied as a model of the mammalian response to radionuclides (Boratyński, Lehmann, Mappes, Mousseau, & Møller, ; Chesser et al., ; Lehmann, Boratyński, Mappes, Mousseau, & Møller, ; Meeks, Chesser, Rodgers, Gaschak, & Baker, ; Meeks et al., ; Rodgers & Baker, ; Rodgers, Wickliffe, Phillips, Chesser, & Baker, ). Baker et al.…”
Section: Introductionmentioning
confidence: 99%